Maternal hemoglobin level and red cell indices as predictors of gestational diabetes in a multi-ethnic Asian population - Tan, P.C.; Chai, J.N.; Ling, L.P.; Omar, S.Z. (2011)
Objective: To evaluate maternal hemoglobin levels and red cell indices as predictive factors for gestational diabetes (GDM). Method: Data from 1,538 women were analyzed. At the first visit for prenatal care, the 50-gram glucose challenge test was followed by the 75-gram glucose tolerance test in those who screened positive. GDM was diagnosed based on the WHO (1999) criteria. Maternal complete blood count was obtained at the first visit, hospitalization for birth, and after birth. Receiver operator characteristic curves were generated to establish thresholds. Multivariable logistic regression analyses were performed to establish independent predictors of GDM. Results: GDM was diagnosed in 182/1,538 (11.8). GDM was associated with hemoglobin level, hematocrit and erythrocyte count at the first visit for prenatal care only. Hemoglobin threshold at the first visit was established at 11.5 g/dl. After adjustment, high hemoglobin AOR 1.5 (95% CI 1.0-2.1); p = 0.027 remained predictive of GDM. Conclusions: High maternal hemoglobin level at the first prenatal visit is independently predictive of GDM.